PROYEK “KRITIK” ABED AL-JABIRI DAN IMPLIKASINYA PADA NALAR KEISLAMAN - Khairiyanto Khairiyanto (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2019)
Critical studies in an academic study are the most important aspects that are ‘necessary’ and ‘required’ to be carried out. The existence of this critical study aims to provide a broad view on a scientific study. The aim is that the study will continue and be developed again. The hope is that there will be a contribution to a civilization of human history. Patterns of excellence and distinctiveness, as a form that knowledge is not entirely final. Abed Al-Jabiri - hereinafter written by Al-Jabiri “through his critical study, tries to offer a concept to the Arabic- Islamic reasoning style. The epistemology of Arabic-Islamic reasoning that has not yet been ‘moved on’ from longstanding history. Al-Jabiri’s criticism of the stagnation of Arab-Islamic reasoning occurs because they have not been able to get out of the ‘lullabies’ of past progress. In addition, he provided a solution so that the Arab community could get out of the chaos that befell it. Through the epistemological framework of “Burhani, Bayani, and Irfani”, he invited the Arab community - we Muslims - to not merely worship the past which was considered complete.